2007
DOI: 10.1002/cncr.23093
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and mortality in men with locally advanced prostate cancer

Abstract: BACKGROUND.Greater body mass index (BMI) is associated with shorter time to prostate‐specific antigen (PSA) failure following radical prostatectomy and radiation therapy (RT). Whether BMI is associated with prostate cancer‐specific mortality (PCSM) was investigated in a large randomized trial of men treated with RT and androgen deprivation therapy (ADT) for locally advanced prostate cancer.METHODS.Between 1987 and 1992, 945 eligible men with locally advanced prostate cancer were enrolled in a phase 3 trial (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 62 publications
3
67
0
Order By: Relevance
“…Prostate cancer patients are surviving for longer periods because of earlier diagnosis and treatment and the long-term consequence of ADT on body composition is becoming increasingly important. A high BMI or weight is thought to be a risk factor for the development of high-grade prostate cancer [38] and metastasis [39] and significantly decreases survival rates and life expectancy [39,40]. Furthermore, a recent large observational study has indicated a relationship between an increased incidence of diabetes, coronary heart disease, myocardial infarction and sudden cardiac death with ADT [41].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer patients are surviving for longer periods because of earlier diagnosis and treatment and the long-term consequence of ADT on body composition is becoming increasingly important. A high BMI or weight is thought to be a risk factor for the development of high-grade prostate cancer [38] and metastasis [39] and significantly decreases survival rates and life expectancy [39,40]. Furthermore, a recent large observational study has indicated a relationship between an increased incidence of diabetes, coronary heart disease, myocardial infarction and sudden cardiac death with ADT [41].…”
Section: Discussionmentioning
confidence: 99%
“…8 • A BMI Ն 35 kg/m 2 may be associated with an increased risk of colon cancer recurrence and mortality, but the data are less consistent. 9,10 • Emerging data suggest that obesity may be a prognostic factor in other malignancies as well.…”
Section: Journal Of Clinical Oncology a S C O S P E C I A L A R T I Cmentioning
confidence: 99%
“…2,3 Specifically, obese men have higher grade Gleason scores, larger tumors and shorter time to PSA failure compared with their lean counterparts. 4 The obesity-cancer progression link may be due in part to dysregulated hormones and obesity-induced inflammation.…”
Section: Introductionmentioning
confidence: 99%